Procedural risk factors for deep and organ/space surgical site infection post-coronary artery bypass graft surgery - Abarna Pearl; Patrick S. Gordon; Baevin S. Feeser; Dana E. Pepe; Preeti Mehrotra; Sharon B. Wright (Cambridge University Press, 2024)
In this study, we examined the impact of the number and type of arterial grafts, and surgical dressing type, on deep and organ/space surgical site infection following coronary artery bypass graft procedures. Bilateral internal mammary artery grafts and negative pressure wound therapy were associated with higher odds of infection.